Cultural industries in Canada: Exploring firm dynamics and measurement - Ryan Macdonald; Josip Lesica; Jenny Watt; Rupert Allen (Economic and Social Reports)
Technological change has led to opportunities and challenges for firms in cultural industries, prompting questions about how these industries have been impacted in Canada. However, there is a lack of information about firms operating in cultural domains. This study attempts to fill this information gap by identifying firms in Canada’s cultural supply chain using administrative data from 2008 to 2020.